DIEL PATTERNS OF FEEDING OF KHISBNI LIZA ABU (HEOKEL) IN RASeOIYAH RESERVOIR IN BAGHDAD, IRAQ - Islam, A K M Sirajul; Khalaf, K N (Indian Journal of Fisheries, 2011)
A single 24-hour feeding cycle of Liza abu from Rashdiyah reservoir, Baghdad, Iraq, was studied. The guts of the fish contained food almost throughout the period and showed two peaks — one at 0600 hours and the other at 2100 hours. Organic matter and detritus formed the major bulk of the diet, followed by diatoms, aquatic plant parts, nematodes, filamentous algae, copepods and aquatic insects. A total of 45 species of algae belonging to 29 genera were observed in the gut of the fish.